Macrophytes of Rajarani-Dhimal Pokhari Wetland, Churia hills, Eastern Nepal - Chaudhary, Rajesh; Niroula, Bhabindra (Nepalese Journal of Biosciences, 2017)
Growth forms, availability and uses of macrophytes found in Rajarani Dhimal Pokhari wetland, Churia hills, eastern Nepal was carried out in 2016. Altogether, 75 species belonging to 64 genera, 30 families, and 7 growth forms were recorded. Growth form classes were: helophytes and hyperhydates (34.7%)> tenagophytes (16%)> pleustophytes (8%) rosulates, epihydates (2.6%)> vittates (1.4%). Nymphea nauchelii, Rorrippa indica; and Cephalanths tetrandra were new aquatic macrophytes to eastern Terai and Nepal, respectively. Aquatic macrophytes useful to local socioeconomy were: feed for livestock (17 sp), edible as pot herbs and wild fruits (5 sp), medicinal (19 sp), green manure/compost (7 sp), fish poison (2 sp), handicrafts as mats/brooms/basketry (8 sp), breeding genetic stock (2 sp) and religious (3 sp). The key species of the wetland Cephalanhus tetrandra is under threat. of Mikania micrantha-an invasive alien species (IAS).